2021
DOI: 10.3389/fped.2020.627122
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Identifies Three Novel Mutations in the ASPM Gene From Saudi Families Leading to Primary Microcephaly

Abstract: Autosomal recessive primary microcephaly (MCPH) is a neurodevelopmental defect that is characterized by reduced head circumference at birth along with non-progressive intellectual disability. Till date, 25 genes related to MCPH have been reported so far in humans. The ASPM (abnormal spindle-like, microcephaly-associated) gene is among the most frequently mutated MCPH gene. We studied three different families having primary microcephaly from different regions of Saudi Arabia. Whole exome sequencing (WES) and Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…The high frequency (10 out of 10 Pashtun families) of the ASPM mutation p.Trp1326 * among Pashtun families hints on its role as a founder mutation among Pashtuns, especially the Wazir tribe, of Pakistan and Afghanistan. Therefore, testing for this mutation, among Pashtuns, as a first step will be a cost-effective and time-saving approach in the future while performing genetic analysis of MCPH families from this and other populations ( 20 ). Similarly, testing for this mutation can also help in population-wide screening for carrier screening and prenatal diagnosis to prevent further affected births.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency (10 out of 10 Pashtun families) of the ASPM mutation p.Trp1326 * among Pashtun families hints on its role as a founder mutation among Pashtuns, especially the Wazir tribe, of Pakistan and Afghanistan. Therefore, testing for this mutation, among Pashtuns, as a first step will be a cost-effective and time-saving approach in the future while performing genetic analysis of MCPH families from this and other populations ( 20 ). Similarly, testing for this mutation can also help in population-wide screening for carrier screening and prenatal diagnosis to prevent further affected births.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The clinical symptoms of our patients are in line with previous reports of ASPM related microcephaly presenting moderate ID, speech impairment, visual abnormalities, seizures, and ptyalism. 4,15,18,19 The mutation CDK5RAP2: c.448C>T p. (Arg150*) segregating in family B is predicted to cause very early termination of the translation. The mutant transcript is predicted to undergo NMD and thus produce no protein.…”
Section: Discussionmentioning
confidence: 99%
“…Missense (n=22) variations were common among the disease variations in the patients with neurogenetic disorders (Figure 3) [40]. RTTN and ASPM genes were associated with primary microcephaly apart from the above listed [40][41][42], Cerebellar ataxia in sibling WES study showed novel variant in CWF19L1 gene [43] and GBA2 gene in consanguineous Saudi family [44]. A study from Qatari subject revealed the association of novel pathogenic PGAP3 variant with global developmental delay and neuromuscular abnormalities and brain anomalies [45].…”
Section: Neurogenetic Disorders and Candidate Genesmentioning
confidence: 98%
“…Protein-protein interaction analysis of genes of intellectual disability candidate genes of Arab population. P r e p r i n t Powered by TCPDF (www.tcpdf.org) P r e p r i n t Powered by TCPDF (www.tcpdf.org) P r e p r i n t Powered by TCPDF (www.tcpdf.org) Powered by TCPDF (www.tcpdf.org) Protein-protein interaction analysis of C12orf57 gene with literature using STRING [42]. C: Protein-protein interaction analysis of genes of intellectual disability candidate genes of Arab population.…”
Section: Legendmentioning
confidence: 99%
See 1 more Smart Citation